Church music inculturation by way of an experiment of arrangement of Dolo-Dolo mass ordinarium accompaniment- composed by Mateus Weruin for woodwind quintet - Ruswanto, Yohanes; Adimurti, Juanita Theresia (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2017)
Inculturation of Church music in an experiment of creating this arrangement aims to bring a different form of musical ordinarium accompaniment form of Dolo-Dolo Mass from Flores, with a different media that uses the woodwind quintet (flute, oboe, clarinet, French horn, and Basson). The experiment took one of the ordinary songs from Madah Bakti â€œTuhan Kasihanilah Kamiâ€. The harmonization fine-tunes to the chorus arrangement composed by Mateus Weruin. The literature study was conducted through collecting references on the art of Dolo-Dolo and woodwind quintet so it can be used to create an idea for this arrangement. The result shows that a rhythmic character that characterizes the traditional Flores music lies in a dotted sixteenth pattern. The richness of sounds and agile characters coming from each instrument creates a percussive atmosphere of Flores folk music. The result of the arrangement experiment can be used to enrich the reference of accompaniment music to the general public and specifically, the Catholic Church.Â